Analisis Materi Pembelajaran Ilmu Pengetahuan Alam dan Sosial Kelas IV Madrasah Ibtidaiyah Perspektif Model Jerold E. Kemp - Alfirdaus, Sinta Khoiriyah; Iswahyono, Akbar Alfian; Hartono, Hartono (IJIT: Indonesian Journal of Islamic Teaching, 2023)
Learning that occurs today is often still transmissive, where students passively absorb the knowledge structure given by the teacher or the material in the textbook. Meanwhile, ideal learning is learning that is able to encourage children's creativity as a whole, make students active, achieve learning objectives effectively and take place in a pleasant condition. Therefore, it takes a learning design model that is appropriate and suitable, especially in learning IPAS class IV. The purpose of this study is to analyze the Natural and Social Sciences material of grade IV Madrasah Ibtidaiyah from the perspective of the Jerold Kemp model. This research uses qualitative research methods and this type of research is included in descriptive research. The results of the study based on the analysis of the material that has been done, namely the flow of learning material in the IPAS module book grade IV semester 1 using constructivism learning theory, the material in the module uses problem-based learning or commonly called Problem Based Learning and there is a lack of concrete illustrative images on the material.